2018
DOI: 10.1111/nicc.12407
|View full text |Cite
|
Sign up to set email alerts
|

Sound isolation and music on the comfort of mechanically ventilated critical patients

Abstract: Objectives To assess the effect of sound isolation versus music on the comfort of mechanically ventilated patients admitted to the intensive care unit (ICU) as a combined measurement of the hypnotic level, the level of sedation and the alteration of behaviour because of pain. Introduction Patients admitted to the ICU who require mechanical ventilation are surrounded by an ambient noise level ranging from 60 to 90 dB, well above the 40 dB recommended by the World Health Organization (WHO). Methods This was a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Table 1 presents the characteristics of the 18 RCTs conducted across seven countries (USA, n = 5; Iran, n = 5; France, n = 2; Spain, n = 2; Turkey, n = 2; China, n = 1; and Australia, n = 1), arranged chronologically from 1999 to 2018 (years of publication). [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Sample sizes ranged from 17 to 156, totaling 1173 participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 presents the characteristics of the 18 RCTs conducted across seven countries (USA, n = 5; Iran, n = 5; France, n = 2; Spain, n = 2; Turkey, n = 2; China, n = 1; and Australia, n = 1), arranged chronologically from 1999 to 2018 (years of publication). [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Sample sizes ranged from 17 to 156, totaling 1173 participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…More specifically, eight RCTs 24,25,[27][28][29][30][31][32] reported a low mean baseline pain score (zero to three of 10) and five RCTs [33][34][35][36][37] reported a moderate pain score (four to six of 10). For the trials that used behavioral scales, two RCTs 26,38 reported their participants' mean baseline behavioral pain scores to be below the cut-point score (i.e. CPOT <3 or BPS <5), and two RCTs 39,40 reported the scores to be above the cut-point scores (CPOT >3 or BPS >5).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the WHO recommends no more than 35 dB of A-weighted energy equivalent (LAeq) SPL during the day and the A-weighted maximum SPL with fast constant (LAFmax) not exceeding 40 dB at night, studies show that LAeqs in most ICUs range from 60 to 90 dB. 41 The ICU environment has evolved over the years to provide information and security. To draw staff attention to potential dangers, acoustic alarms have become commonplace.…”
Section: Sound and Icu Environmentmentioning
confidence: 99%
“…The issue of excess noise pollution within critical care environments is also addressed by Mateu‐Capell et al . (), who undertook a randomized crossover clinical trial with 82 mechanically ventilated ICU patients to assess the effectiveness of two interventions in reducing noise levels. Using noise‐cancelling headphones, Group A ( n = 42) underwent sound isolation for an hour, followed by an hour of music.…”
mentioning
confidence: 99%